Inhibitory activity against carbonic anhydrase IX and XII as a candidate selection criterion in the development of new anticancer agents. (1st January 2020) - Krasavin, Mikhail; Kalinin, Stanislav; Sharonova, Tatiana; Supuran, Claudiu T.
Abstract: Analysis of the literature data reveals that while inhibition of cancer-related carbonic anhydrase IX and XII isoforms continues to be an important enrichment factor for designing anticancer agent development libraries, exclusive reliance on the in vitro inhibition of these two recombinant isozymes in nominating candidate compounds for evaluation of their effects on cancer cells may lead not only to identifying numerous compounds devoid of the desired cellular efficacy but also to overlooking many promising candidates which may not display the best potency in biochemical inhibition assay. However, SLC-0111, now in phase Ib/II clinical trials, was developed based on the excellent agreement between the in vitro, in vivo and more recently, in-patient data.